Effect of Seedling Age and Method of Transplanting on the Yield of Aman Rice (Progressive Agriculture, 2014)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh from June to December 2012 with a view to finding out the effect of seedling age and method of transplanting on the yield of Aman rice. Four seedling ages (10, 20, 30 and 40 days) and two transplanting methods (line and haphazard) were used as experimental treatments with four replications in a randomized complete block design. Seedling age, transplanting method and their interaction significantly influenced most of the yield components and yield of transplant Aman rice cv. BRRI dhan41. The highest total tillers, effective tillers hill-1, grains panicle-1, grain yield, straw yield and harvest index were obtained from 30-day-old seedlings. Line transplanting method produced the highest total tillers, effective tillers hill-1, grain yield and harvest index. The highest total tillers, effective tillers hill-1, grain yield and harvest index were obtained from 30-day-old seedlings with line transplanting method. Results revealed that 30-day-old seedlings under line transplanting method could be used to obtain maximum yield of transplant Aman rice cv. BRRI dhan41.DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19092 Progress. Agric. 24(1&2): 9 - 16, 2013